BISIKAN DARI BALIK LAYAR: NETNOGRAFI STRATEGI BISNIS BERORIENTASI PASAR - Edi Purwanto; John J.O.I. Ihalauw (Journal of Business & Applied Management, 2016)
Netnography is an interpretative approach to study consumer behavior from different cultures andcommunities in the cyberspace or Internet. The approach was also called as a “digital ethnography”or “virtual ethnography”. As a marketing research technique, “netnography” uses the informationsources published in the online forums. This research uses the reviews on zomato.com as a source ofdata to assess the market orientation development in business practice, especially at Restaurant X.The result of netnography analysis indicates that customer orientation, competitor orientation, interfunctionalcoordination and long-term focus are the dimensions of market orientation and should bedeveloped for customer satisfaction and loyalty leading forward to the business performance.